Islamic Banking Efficiency and Sharia Compliance: Comparative Insights from Indonesia and Malaysia - Pratama, Versiandika Yudha; Suryo, Ibnu; Rismawati, Shinta Dewi; Devy, Happy Sista; Tamamudin, Tamamudin (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
The rapid expansion of Islamic banking in Southeast Asia has positioned Indonesia and Malaysia as central actors in the global Islamic finance landscape. However, despite their shared religious and economic foundations, structural differences in regulatory frameworks, financial innovation, and market development have produced varying levels of institutional performance and sharia compliance. This study aims to compare the financial and sharia performance of Islamic commercial banks in both countries by employing the Sharia Conformity and Profitability Index (SCnPI), which integrates sharia compliance indicators—Zakat Performance Ratio (ZPR), Profit Sharing Ratio (PSR), and Islamic Income Ratio (IIR)—with profitability indicators—Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Using a quantitative comparative design, the study analyzes secondary data from 25 Islamic commercial banks (12 from Indonesia and 13 from Malaysia) for the 2022–2023 period, selected through purposive sampling. Data were analyzed using the Shapiro–Wilk test for normality and either the independent sample t-test or Wilcoxon signed-rank test for mean comparison. The results indicate significant differences in PSR and NPM, with Indonesia showing higher PSR values due to dominant musyarakah-based financing, and Malaysia exhibiting higher NPM, reflecting stronger cost efficiency and profit management. Other indicators show no statistical difference. These findings emphasize the influence of governance systems and managerial focus on financial outcomes and suggest that improving transparency, risk-sharing mechanisms, and operational efficiency could enhance Islamic banking resilience across the region. Abstrak Efisiensi dan Kepatuhan Syariah dalam Perbankan Syariah: Analisis Komparatif dari Indonesia dan Malaysia. Perkembangan pesat perbankan syariah di Asia Tenggara menempatkan Indonesia dan Malaysia sebagai dua negara utama dalam industri keuangan Islam global. Namun, meskipun memiliki dasar ekonomi dan religius yang serupa, perbedaan dalam kerangka regulasi, inovasi keuangan, dan tingkat kematangan pasar menyebabkan variasi dalam kinerja institusional dan kepatuhan terhadap prinsip syariah. Penelitian ini bertujuan membandingkan kinerja keuangan dan kepatuhan syariah bank umum syariah di kedua negara dengan menggunakan Sharia Conformity and Profitability Index (SCnPI), yang mengintegrasikan indikator kepatuhan syariah—Rasio Kinerja Zakat (ZPR), Rasio Bagi Hasil (PSR), dan Rasio Pendapatan Syariah (IIR)—dengan indikator profitabilitas—Return on Assets (ROA), Return on Equity (ROE), dan Net Profit Margin (NPM). Penelitian kuantitatif ini menggunakan data sekunder dari 25 bank umum syariah (12 dari Indonesia dan 13 dari Malaysia) periode 2022–2023 yang dipilih melalui metode purposive sampling. Analisis data dilakukan menggunakan uji normalitas Shapiro–Wilk dan uji komparatif t-test sampel independen atau uji peringkat bertanda Wilcoxon. Hasil penelitian menunjukkan perbedaan signifikan pada PSR dan NPM, di mana bank syariah Indonesia memiliki PSR lebih tinggi karena dominasi pembiayaan musyarakah, sedangkan Malaysia memiliki NPM lebih tinggi yang mencerminkan efisiensi biaya dan manajemen laba yang lebih baik. Indikator lainnya tidak menunjukkan perbedaan signifikan. Temuan ini menegaskan pengaruh sistem tata kelola dan orientasi manajerial terhadap kinerja keuangan serta pentingnya peningkatan transparansi, mekanisme bagi hasil, dan efisiensi operasional dalam memperkuat ketahanan perbankan syariah di kawasan.